2012
DOI: 10.1590/s1807-55092012000400009
|View full text |Cite
|
Sign up to set email alerts
|

Profile of physical activity in daily life in physically independent elderly men and women

Abstract: This study compared the profile of daily activities and variables of functional fitness between elderly men and women, as well as the relation of their time spent walking per day with the remaining study variables concerning each gender. Thirty healthy elderly (15 men; 66 ± 6 years), sedentary and physically independent, had their daily activities evaluated objectively by a multi-axial accelerometer as well as their metabolic and functional fitness variables by means of specific protocols. Both men and women p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
1
1
0
2
Order By: Relevance
“…Despite the protocol including activities that are more common to women's routine due to the presence of domestic tasks, men can perform similar movements, during work activities. Teixeira et al 27 showed that there was no difference in time spent walking per day between women and men Ͼ60 y old, corroborating the present findings.…”
Section: Discussionsupporting
confidence: 91%
“…Despite the protocol including activities that are more common to women's routine due to the presence of domestic tasks, men can perform similar movements, during work activities. Teixeira et al 27 showed that there was no difference in time spent walking per day between women and men Ͼ60 y old, corroborating the present findings.…”
Section: Discussionsupporting
confidence: 91%
“…Elderly women remain significantly longer standing than men. 38 This posture is probably stimulated by a greater demand that women perform household activities often carried out in a standing position, such as washing, ironing, and cooking. 38 These activities, which are present in higher amounts in women's daily lives, can also exert influence on their balance.…”
Section: Differences According To Sexmentioning
confidence: 99%
“…Um estudo realizado com indivíduos entre 20 e 85 anos, demonstrou que aqueles que apresentaram um baixo escore de IID e que se declararam ativos, tiveram uma redução de 39% no risco de mortalidade por todas as causas (OR=0,61; IC95%: 0,49-0,76), quando comparados àqueles com maior IID e estavam inativos (EDWARDS et al, 2018 2017) IMC: Índice de Massa Corporal (com excesso de peso: ≥25 kg/m²; sem excesso de peso: ≤24,9 kg/m²), FID: Fator Inflamatório da dieta: avaliado no software Smartdiet A Tabela 2 mostra a associação da prática de exercício física, índice de massa corporal e o fator inflamatório da dieta. Foi observado diferença no sexo entre os dois grupos, diferente ao encontrado em estudo anterior (TEIXEIRA et al, 2012). Entretanto não houve diferença em relação ao IMC e FID.…”
Section: Resultsunclassified